The Impact of the Large-Scale Social Restriction on Student Behavior - Nurkholis Nurkholis; Atabik Atabik; Dianasari Dianasari; Amanda Retno Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The coronavirus that hits Indonesia at this time has greatly affected people’s activities especially the field of education. The stipulation of the Large-Scale Social Restriction (LSSR) to address this condition has generated a new learning policy and behavioral changes. This study aims at analyzing the form of policy and the impact of the LSSR and the phenomenon of changes in student behavior during the implementation of the PSBB policy in the RA Kartini Cluster. In this study, researchers used qualitative methods with descriptive analysis and case study approaches. Subjects of this study were teachers and students of Grades I-VI of Gugus RA Kartini. Results indicated that the LSSR implemented at Gugus RA Kartini affected the learning policy regarding offline learning. Besides, the LSSR also caused several bad effects, such as making students less diligent and less interested, changes in discipline, honesty, social care, communication, and religious behaviors. With the findings of this study, it is advisable that the policy of implementing LSSR needs to be considered immediately. But, this research can be said to be limited only to the impact caused by the implementation of LSSR, so that this research can be developed based on other aspects that support the effectiveness of learning and changes in student behavior.